An alternative marker of inflammation in parenteral nutrition: IMA - Timurkaan, Mustafa; Altuntas, Gulsum; Kalayci, Mehmet; Timurkaan, Esra Suay; Ayyildiz, Hakan; Dalkilic, Semih (Bayrakol Medical Publisher, 2022)
Aim: There is an increase in inflammation and metabolic complications in patients receiving PN. Because of inflammation and oxidative stress, an increase in IMA levels can be observed. We aimed to evaluate the effectiveness of detecting IMA and other inflammatory parameters in modulating nutritional therapy of critically ill patients. Material and Methods: A total of 83 subjects were divided into two groups: 41 receiving PN (F:20, M:21) and 42 receiving EN (F:22, M:20). Patients over the age of 18 whose NRS 2002 score was <3, and who were followed up in the intensive care or palliative care units were included. CBC, glucose, protein, albumin, ferritin, CRP, electrolytes, and IMA levels were compared. Results: There was a difference in CRP values in the group receiving PN compared to the group receiving EN (p=0.001). NLR and CRP/albumin were found to be higher in the PN group (p <0.05 and p <0.01). IMA levels were also found to be significantly higher in the PN group compared to the enteral group (p <0.01). Discussion: Compared with EN, inflammation, metabolic and oxidative stress can occur in patients receiving PN. Increased inflammatory parameters and IMA levels are important in terms of additional treatment modalities to nutrition. This oxidant process can be prevented by using antioxidant support such as vitamins and minerals, emulsions containing olive oil, and omega-3 fatty acids. IMA and inflammatory parameters can be guiding as predictors of this process.
Keywords: Nutrition; Enteral; Parenteral; IMA; Hyperinflammation